PARTISIPASI PEREMPUAN, EDUKASI TENTANG PEMILU DI PKK BANJAR PUCAK SARI DESA DANGIN PURI KAUH - Putri, Ni Ketut Lisa Alfina Putri; Ekaresty Haes, Putri; Aflah Ramadiansyah, Sahri; Rahayu Gorda, Anak Agung Ayu Ngurah Sri; Adriati, I Gst Ayu Wirati (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2024)
Women's participation in democracy in Indonesia has historically faced challenges, especially at the local level such as in villages. PKK (Family Welfare Empowerment) had great potential as a forum for women's participation, but education on elections and active roles in democracy was often inaccessible to them. Community service activities was one form of community service by university students that could be used to enhance peaceful election education in PKK Banjar Pucak Sari Village, Dangin Puri Kauh. Through this program, women were expected to become active agents of change in disseminating democratic values and campaigns for peaceful elections through social media. Community service activities involved discussions, experimentation with link and barcode creation, brochure preparation, and training in using social media for peaceful election campaigns. Informative and engaging brochures on peaceful election education were also created and distributed to the public. Thus, it was hoped that women's participation in local elections and politics would be increased, creating a more inclusive and representative society. This study identified challenges and solutions in program implementation, providing a comprehensive overview of implementation stages, methods, challenges, and solutions. The results were expected to serve as a guide for other institutions or organizations wishing to implement similar programs to enhance women's participation in democracy.Keywords: Women's Participation, Democracy, Election Education, PKK, Community Service Activities.